STABILITY BASED HPLC METHOD FOR CYCLOPHOSPHAMIDE RELATED SUBSTANCES IN FINISHED DRUG PRODUCTS: DEVELOPMENT AND VALIDATION - JOTHULA, HARIBABU; NAVULURI, SRINIVASU; MULAKAYALA, NAVEEN REDDY (International Journal of Current Pharmaceutical Research, 2024)
Objective: The current study aimed to develop a simple, sensitive, and precise high-performance liquid chromatographic (HPLC) method for estimating cyclophosphamide and its related substances, as well as to implement the developed method in a capsule product. Methods: Method development was performed using various solvent and buffer-solvent ratios at different flow rates for better resolution and to decrease the run time. The developed method was validated in accordance with the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) guidelines. The developed method was implemented to estimate the amount of cyclophosphamide and its related substances. Results: Chromatographical conditions were optimised, and the best chromatographical conditions with adequate resolution for cyclophosphamide and its related substances were achieved using the enable X-Bridge C18 column, using a mobile phase combination of phosphate buffer pH 7.0, water, methanol, and acetonitrile at a flow rate of 0.5 ml/min. The detection was monitored at a wavelength of 200 nm. The developed method was validated for system suitability, specificity, limit of detection (LOD), limit of quantitation (LOQ), linearity, precision, accuracy and robustness. The results indicate that the method was sensitive and could detect and quantify lower levels of cyclophosphamide and its related substances. The linearity range was from LOQ to 150 %, and a correlation coefficient ranging from 0.9987 to 0.9999 indicates that at this concentration range, substances were highly linear. This was further supported by satisfactory forced degradation studies. Conclusion: The developed analytical method is simple, precise, and reproducible and thus can be used for the stability-indicating analysis of cyclophosphamide and its related substances in pharmaceutical formulations.